Development of a Reduced Methyl-cyclohexane Model for Diesel Engine Applications - Tan, Johnin (2019)
Cyclo-alkanes are the major constituents of hydrocarbons in market fuels such as petrol, diesel, and aviation fuels. Diesel fuels derived from bituminous sands have up to 35 % of cyclo-alkanes. Furthermore, cyclo-alkanes play an important role in soot formation because they yield aromatic compounds through dehydrogenation. Hence, it is crucial to include cyclo-alkanes in diesel surrogate fuel models. As a result, better prediction in the combustion and emission simulations can be achieved. The aim of this study was to develop a reduced methyl-cyclohexane (MCH) model for diesel engine applications. In this study, the detailed MCH model with 1 540 species was served as the base model. The reduced MCH model was derived by performing mechanism reduction. Consequently, the reduced model with 86 species, namely MCHv1 was successfully derived after elimination of unimportant species. Next, MCHv1 was validated against detailed model with respect to ignition delay (ID) timings and species profiles in zero-dimensional (0-D) simulations. Computed results by MCHv1 were in close agreement with the detailed model. Maximum deviation in ID timings is only 28 %. Furthermore, the reduced model was validated against experimental results for jet-stirred reactor (JSR) and auto-ignition conditions. Simulated results using the reduced model were in close agreement with experimental data. Moreover, a reduced diesel surrogate fuel model with 144 species, namely D_144 was developed and MCHv1 was used to represent cyclo-alkanes. Lastly, D_144 surrogate model is ready to be used for parametrically study of combustion and pollutant formation in three-dimensional (3-D) internal combustion engine simulations and two-dimensional (2-D) spray combustion simulations.